RANCANG BANGUN ANIMASI PERCAKAPAN BAHASA INGGRIS BERBASIS 2D MENGGUNAKAN TEKNIK FRAME BY FRAME - Hasanuddin, Hasanuddin; Agus Jayadi; Putri Ayu Firmansani (Department of Information System Muhammadiyah University of Riau, 2022)
This research focuses on the Animation Design of “English Conversation”2D Based Using Frame By Frame Technique. The purpose of this research is to facilitate teacher in delivering English conversation material and to increase interest student learning and increase enthusiasm for learning. The method used is the method research and development (R&D) which can be defined as “a scientific way of researching, designing, producing and testing questionnaires and product validity that have been generated